ARGAMASSA PARA CONTRAPISO AUTONIVELANTE COM ADIÇÃO FINA DE ESCÓRIA DE COBRE BATIDA - Santos, Rafaela; Melo, Fernando; Sales, Daniel (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Environmental preservation is a widely discussed topic throughout society, due to heavy reliance on natural resources for survival on the planet. Rational use of raw materials and their proper disposal are on the agenda of the productive sectors’ major concerns. The present paper aims to evaluate the feasibility of application of copper production waste, called copper slag, after being used as abrasive material in blasting services, renamed blasted copper slag. Therefore, this residue was sieved in the 75 μm mesh sieve. The blasted copper slag application was studied as thin addition in mortars for self-leveling floor. This mixture showed a 24 cm spreading and a flow time of eight seconds, satisfying the required parameters of EFNARC. Results of the flexural strength tests showed that there was a reduction of 57% of resistance for the self-leveling mortar, with copper residue, compared to the conventional mortar.